A study on management of premature rupture of membranes - Mondal, Arnab; Kanoongo, Sanhita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Premature rupture of membranes (PROM) is a common obstetric complication. Knowledge of etiopathogenesis, diagnosis, complications and management of PROM has significantly increased due to extensive research in the recent past. Yet, there is no unanimous opinion regarding optimum management of PROM. The aim of the study was to observe the patients during labor and compare the latent period, duration of first stage of labor, modes of deliveries and the use of oxytocin and its outcome in PROM cases with controls. The study has been conducted with the belief that these data will help in better management of PROM cases in future. Methods: In this study, the definition of PROM adopted is rupture of fetal membranes before the onset of true labor pain. The minimum gestational age was taken to be 28 weeks. Diagnosis of PROM was mainly clinical. Patients were monitored during the latent period and during labor. Induction of labor was done where necessary. Collected data were analysed using Chi Square Test. Results: It was observed that onset of labor was more rapid with increasing gestational age. Use of oxytocin for induction and augmentation of labor and operative deliveries were higher in PROM cases. These results mostly corroborated with the findings of other researchers. Conclusions: The conclusion drawn at the end of the study was that individualized management of PROM cases depending on the gestational age and risk of complications is the best way to achieve a good fetomaternal outcome.